Efficacy of Split-Dosing versus Conventional Bowel Preparation in Colonoscopy: A Randomized Clinical Trial - Gee, Tikfu; Abdullah, Nadia B; Wai Peng, Chin; Sheau Wan, Tong; Oominn, Minn; Shu Yu, Lim; Fei Yee, Lee; Nik Qisti, Fathi; Xin, Lim Wan; Yue, Tsen Poh (International Journal of Innovative Research in Medical Science, 2018)
Background: Colonoscopy is an indispensable investigative and therapeutic tool in colorectal conditions. The accuracy of colonoscopic diagnosis is dependent on the effectiveness of the bowel preparation and the visibility of the colonic mucosa. Objective: This study compares the efficacy of split-dosing bowel preparation compared to the conventional the single-day timing of bowel preparation, by measuring the quality of colonoscopy performed using a validated bowel cleanliness score. Methods: An endoscopist-blinded clinical trial was conducted over a period of three months through convenient sampling at the Surgery Out-Patient Clinic at a secondary referral hospital in Malaysia. Data were recorded prospectively on the timing of bowel preparation, colonoscopic view of bowel cleanliness, age, and gender. Results: There was a total of 110 subjects for both conventional and test groups. Demographic studies showed 63 (57.3%) patients were under 60 years old, 61(55.5%) were male, and 48 (44%) were Malays. For the patients undergoing colonoscopy, the majority of the 86 (78.2%) had good bowel preparation and 96 (87.3%) of them with high efficacy of bowel preparation. The timing of bowel preparation is significantly associated with the efficacy of the bowel preparation and the quality of the colonoscopy (p<0.05). Conclusion: We conclude that split-dosing bowel preparation is significantly better than conventional timing bowel preparation in improving both the efficacy of bowel preparation as well as the quality of colonoscopy.